The Band Structure of Polycrystalline Al2O3 and Its Influence on Transport Phenomena. Issue 3 (10th February 2016) - Heuer, Arthur H.; Zahiri Azar, Maryam; Guhl, Hannes; Foulkes, Matthew; Gleeson, Brian; Nakagawa, Tsubasa; Ikuhara, Yuichi; Finnis, Mike W.
Abstract : The electronic (band) structure of polycrystalline Al2 O3, in particular the density of near‐band edge grain‐boundary localized states, plays a significant role in a host of high‐temperature phenomena, including sintering, high‐temperature creep, oxygen permeability in dense "dry" Al2 O3 ceramics, and Al2 O3 scale formation on Al2 O3 scale‐forming alloys. All these phenomena involve creation or annihilation of charged point defects (vacancies and/or interstitials) at grain boundaries and interfaces, and must of necessity involve electrons and holes. Thus, the density of states associated with grain boundaries in Al2 O3 assume great importance, and has been calculated using DFT for both nominally undoped and Y‐doped Σ7 bi‐crystal boundaries. These quantum mechanical calculations must be taken into account when considering why Y2 O3 segregation to Al2 O3 grain boundaries is so effective in enhancing high‐temperature creep resistance of polycrystalline Al2 O3, and in understanding the reactive element effect in Al2 O3 scale‐forming alloys. Finally, a case will be made that grain‐boundary diffusion is mediated by the migration of a class of grain‐boundary ledge defects called disconnections, which are characterized by a step height h and a Burgers vector b.